ESTUDIO ECOLÓGICO DE LAS CECIDIAS DEL GÉNERO SCHINUS, ESPECIALMENTE LAS DE HOJA Y DE RAMA DE 5. POLYGAMUS Y S. LATIFOLIUS (ANACARDIACEAE), EN CHILE CENTRAL - Sáiz, Francisco; Núñez, Carlos (Acta Entomológica Chilena, 2022)
This paper is organized in two parts: a) cecidia identification in the genus Schinus; b) biological description of the development of cecidia in leaves and twigs of Schinus polygamus and S. latifolius. Fourteen different kind of cecidia were detected in Schinus, seven of which were described for the first time. S. polygamus was the most affected. The relationships between incidence of cecidia, age of plants and anthropic intervention were tested. Related to cecidia in leaves and twigs of S. polygamus and S. latifolius, the following aspects were analyzed, throughout an annual cycle: size and color of cecidia, “cecidia per leaf ’ ratio, size, biological aspects of gall-makers and parasitoids, relationships between the life cycle of cecidogenous insects and the phenology of plants. All cecidia analyzed were induced by Psylloidea (Hemiptera). Those of leaves by Calophya mammifex and those of S. polygamus twigs by Taynaris sórdida and Calophya rubra. The life cycle of Psylloidea in leaves was univoltine and probably bivoltine in twigs, with reinfection by the later nymphal stage. The cecidia in twigs of S. polygamus present two morphological shapes: spherical in winter and conical in summer.